FINGER PAINTINGDENGAN PEWARNA AROMA BUAH-BUAHAN: TERAPI DALAM UPAYA PENINGKATAN KEMAMPUAN MOTORIK HALUS BAGI ANAK BERKEBUTUHAN KHUSUS - Yulianto, Yulianto; Dite, Stri Agneyastra; Zarkasi , Sofwan (Institut Seni Indonesia Surakarta, 2024)
The ‘Anugerah Aulia’ Inclusive Art Studio is an integrated service space for the growth and development of Children with Special Needs (ABK) that assists parents in finding problems in children precisely and accurately so that management is obtained following the needs of ABK and family. The problem faced is that there are still many ABK residents around the studio who are not willing to join. The studio's main indication of activities or services in general, namely, tending to basic therapist activities. Skill-based activities that can improve the abilities of ABK, more specifically in the field of fine arts as a means of self-development, are still very minimally carried out. The Finger Painting Workshop with fruit scent dyes was carried out to provide direct motivation to people with disabilities, especially to improve the fine motor skills of children with special needs. The method used in this workshop activity applies a multi-sensory method with a play approach. The workshop activities are designed to have a holistic positive impact: 1) the organizers get space to do community service on the knowledge that has been discovered and processed in the campus laboratory; 2) ABK friends fostered by the ‘Anugerah Aulia’ Inclusive Studio gained knowledge; experience, art therapy, work and motivation to continue to be creative 3) studio administrators acquire knowledge upgrading to be provided to remap services based on art therapy or skills in the field of fine arts; 4) The works produced by ABK in this workshop can be present as a trigger for the birth of creative and aesthetic products collected in the AuliaAward Inclusion Studio service